Skin Closure in Laparoscopic Living Donor Nephrectomy: Modern Tissue Adhesive versus Conventional Intracutaneous Suture—A Randomized Study. (9th March 2014) - Vormdal, Silje Marie; Skauby, Morten; Lonar, Silje; Øyen, Ole
Abstract : Purpose . To compare the modern tissue adhesive cyanoacrylate (Liquiband) to conventional, intracutaneous suture and dressing, with regard to wound characteristics, time consumption, donors' self-satisfaction, and cost. Methods . Sixty-four kidney donors, subjected to laparoscopic hand-assisted nephrectomy, were randomly assigned to skin closure either with tissue adhesive (n = 32 ) or suture (n = 32 ). The follow-up assessments were carried out on postoperative days 2, 4 and at departure, evaluated by the use of a previously set numerical scale for rubor, secretion, gaps, oedema, and blisters. Infections and complications/reinterventions were recorded, as well as operative/skin closure time and costs. The donors' self-satisfaction was evaluated by means of a questionnaire. Results . There were significant results in favour of tissue adhesive regarding wound closure time and the wound characteristics "rubor, " "blisters, " and "oedema." Although, the wound parameters "secretion" and "gaps" altogether showed a rather evident tendency in favour of suture, partially at significant levels. A low rate of complications/reoperations/infections did not give rise to any significant differences. Conclusion . Our study concludes that gluing is significantly faster, less traumatic by avoiding needle penetrations, but associated with an increased rate of secretion and gaps—presumably depending on gluing technique. Glue seems particularly suitable for small, laparoscopic/trocar incisions.